남북 농업교류협력 10년: 평가와 과제 - 김영훈 (한국농촌경제연구원, 2007)
The purpose of this research is stated as in below. The first purpose is to categorize North and South Korea's agricultural cooperations that have been promoted since mid-1990's, and to show present circumstance. The second is to summarize the achievements and problems of the cooperation for last 10 years. The last purpose is to suggest new direction and tasks in order to correspond to the recent environment of expanding economic cooperations between South and North Korea. This research is consist of four parts. In the first part, The food and agricultural crisis of North Korea in mid-1990's is stated. And also, the South Korean cooperation policy toward North Korea is mentioned to clarify the background of the agricultural cooperation works. Second part is concerned with the conditions of agricultural cooperations. The main contents included in this part are support from non-government organizations, trade and commercial business of agricultural secter, governmental aid from South Korea, and agricultural cooperations under agreement between both governments. In the third part, each kinds of cooperations were evaluated by its accomplishments and problems. In addition, current situation of North Korean agriculture such as food supply, agricultural structure, resource supply and the basis of agriculture are compared with those of mid-1990's In the conclusion, new direction and assignments of agricultural cooperation between North and South Korea that would be suitable for new environment is suggested.